Parental attention toward students of SMAN 1 Ulakan Tapakis - Solina, Wira (Jurnal Konselor, 2015)
The purpose of this research is to figure out portray of parentsâ attention toward studentsâ learning and their daily lives in SMAN 1 Ulakan Tapakis. This research used a descriptive quantitative approach. The sample of the research was the tenth and eleventh graders at SMAN 1 Ulakan Tapakis, which consisted of 156 students. It employed sampling proportionate stratified random sampling technique. The instrument used was Likert Scale. The results of reliability test stated that parental attention was 0,888. The results of the validity of the average an instrument parental attention was 0,559.The findings showed that parental attention on average was categorized as pretty good.Keywords: Attention, Parents